2018
DOI: 10.5812/semj.67806
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Organizational Leadership Style and Musculoskeletal Injuries Among Workers of an Iranian Process Industry

Abstract: Background and Objectives: The organizational leadership style can be considered as an important psychosocial factor that may affect workers' health, safety, and productivity. The current study aimed at investigating the relationship between organizational leadership style and musculoskeletal disorders (MSDs) among workers. Methods: The current descriptive, cross sectional study was conducted on 188 employees, including 10 leaders and 178 followers of an Iranian process industry. Nordic MSDs questionnaire (NMQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…2 Despite the high prevalence of MSDs in communities, healthcare personnel are faced more with these problems. 14,15 Various investigations have shown that work-related disorders were one of the basic problems among healthcare personnel. Yet, the individuals who had direct contact with patients, specifically nurses and operating room personnel, were more involved with these disorders.…”
Section: Introductionmentioning
confidence: 99%
“…2 Despite the high prevalence of MSDs in communities, healthcare personnel are faced more with these problems. 14,15 Various investigations have shown that work-related disorders were one of the basic problems among healthcare personnel. Yet, the individuals who had direct contact with patients, specifically nurses and operating room personnel, were more involved with these disorders.…”
Section: Introductionmentioning
confidence: 99%
“…11 Nursing staff suffers the most from LBP, which is one of the fundamental issues. [12][13][14][15] The frequency of LBP among nurses, however, varies from 40% to 90% worldwide. [16][17][18] The frequency of LBP among nurses in Africa ranges from 44.1% to 82.7%, according reviews done between 2000 and 2018.…”
Section: Introductionmentioning
confidence: 99%